2018
DOI: 10.1121/1.5084038
|View full text |Cite
|
Sign up to set email alerts
|

An acoustic camera approach to studying nasality in speech: The case of Polish nasalized vowels

Abstract: The purpose of this research is to introduce an acoustic camera method to analyze nasality in speech. The input information is generated using an acoustic camera device composed of a 16-channel audio recorder with a microphone array, a high-speed video camera, and Carstens articulograph (model AG500). The linearly constrained minimum variance algorithm is used to provide illustrations of the spatial acoustic field distribution. Acoustic pressure distribution is determined as related to the location of oral, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Additionally, when synergized with machine learning, this method can devise optimal, patient-specific therapy to correct speech disorders. It is noted that while several studies have used schlieren imaging to study speech flows [ 26 , 29 , 30 ], none have applied it to speech therapy, focusing instead on the flow intensity of nasal/oral vowels in different languages (German [ 26 ], Polish [ 29 ], and French [ 30 ]). Harvey et al [ 31 ] attempted to recover physical audio signals from high-speed schlieren images, but this approach may be limited to shockwaves generated by events such as clapping hands, snapping belts, and cracking towels, where high-frequency signals dominate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when synergized with machine learning, this method can devise optimal, patient-specific therapy to correct speech disorders. It is noted that while several studies have used schlieren imaging to study speech flows [ 26 , 29 , 30 ], none have applied it to speech therapy, focusing instead on the flow intensity of nasal/oral vowels in different languages (German [ 26 ], Polish [ 29 ], and French [ 30 ]). Harvey et al [ 31 ] attempted to recover physical audio signals from high-speed schlieren images, but this approach may be limited to shockwaves generated by events such as clapping hands, snapping belts, and cracking towels, where high-frequency signals dominate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the flow variations following lip closure, as described in other studies [ 27 , 28 ]. Lorenc et al [ 29 ] used an acoustic camera approach to investigate Polish nasalized vowels and suggested that the acoustic pressure distribution was dependent on the resonance location (i.e., nasal, oral, velopharyngeal, etc.). The sequence and percentage share of oral and nasal resonances were also determined from the acoustic field of Polish nasalized vowels.…”
Section: Introductionmentioning
confidence: 99%
“…Gąsiorek's data were recorded and collected on an analogue device. It has been found that the colloquial speech test, containing only oral sounds (test VII), correlates best with the degree of nasalance [10]. In general, the results obtained by Gąsiorek averaged 15.2% while in colloquial speech they averaged 25.6% [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Wprowadzenie badań obiektywnych do diagnostyki zaburzeń mowy jest szczególnie przydatne nie tylko przy stawianiu rozpoznania, lecz także w celu usprawnienia procesu leczniczo-rehabilitacyjnego [4]. Jak wynika z przeglądu literatury, dostępne są coraz nowocześniejsze metody oceny mowy [17,18]. W praktyce klinicznej na oddziałach otolaryngologicznych i foniatrycznych najczęściej stosowane są metody akustyczne i ciśnieniowo-akustyczne.…”
Section: Wynikiunclassified